Industrial high power electron accelerator for the energy 5-10 MeV - Auslender, V.L.; Bazhenov, O.Yu.; Cheskidov, V.G.; Karliner, M.M.; Kuznetsov, G.I.; Makarov, I.G.; Ostreiko, G.N.; Panfilov, A.D.; Tiunov, M.A.; Tkachenko, V.O. (Вопросы атомной науки и техники, 2001)
This paper presents the project of an industrial accelerator of the modular structure. Accelerating structure consists of the chain of coaxial ILU cavities, connected by the coupling cavities. Two designs of accelerating structure, differing by a version of coupling cavities, are presented. Main parameters of the accelerator are: energy of electrons 5-10 MeV, average beam power up to 150 kW, operating frequency 176 MHz, duty factor 10%.